Penyuluhan Pengolahan Sukun Menjadi Beberapa Jenis Olahan Makanan pada Kelompok Tani Amanah, Desa Cipanileman, Kecamatan Cileunyi, Kabupaten Bandung - Nataliningsih Nataliningsih; Gijanto Purbo Suseno; Edang Juliana (LPPM Universitas Koperasi Indonesia, 2023)
The purpose of this community service activity program is to provide a solution for the people of Cipanileman Village to process breadfruit into several types of processed food so as to produce added value which has an impact on increasing the income of farmer groups. Presentation of material is carried out using lecture, question and answer, discussion, demonstration, assignment, and participatory methods. As a tool to understand the stages of processing, images containing processing stages or two-dimensional media are used, while direct demonstrations are used to improve skills. The material presented consisted of: processing breadfruit into shredded breadfruit, processing breadfruit into cookies, and processing breadfruit into cakes. The enthusiasm of the participants in participating in the counseling was quite high in participating in the training. Counseling on breadfruit processing into floss, cookies, and cakes, can be developed to open new businesses in the field of food processing. Therefore, further, development is needed so that the pioneering business of processing breadfruit into floss, cookies, and cakes can run and develop smoothly. Needs analysis still needs to be improved. In addition to technical training, counseling is also provided relating to understanding Entrepreneurship and Selling Price Calculations, as well as Understanding Cooperatives. The implementation of field coaching (assistance) needs to be carried out in order to increase the effectiveness of the training.